Simple printed array for microwave power rectenna - Esa, M.; Jasman, M. R.; Subahir, S.; Mustafa, M. W.; Taha, F.; Hussin, F. (ieee, 2000)

(untitled)
A simple printed Yagi-Uda antenna (YUDE) operating at 2.45 GHz is proposed in this paper for wireless microwave power transmission. The antenna has an electromagnetic coupling feed, through a printed power splitter/combiner. The antenna is compared with two corresponding single structures having coaxial (YUSC) and electromagnetic coupling feed (YUSE), respectively. All antennas are well-matched at the corresponding frequency of operation with -10 dB reflection bandwidth of less than 2%. The antennas exhibit directional far-field E-plane radiation pattern. YUDE has the smallest 3 dB beamwidth indicating the highest directivity. The relative gain of the YUSE was found to be 7 dB better than YUSC. However, YUDE showed the least relative gain. This could be due to the imperfect feed location of the power splitter/combiner which was rather difficult to be achieved